Martensite transformation behavior and mechanical properties of two kinds of low‐nickel austenite stainless steel. Issue 7 (8th July 2022) - Cai, C.; Wu, H.; Liao, L.; Li, J.; Chen, Y.
Abstract: In this study, tensile tests were performed to study the effect of martensitic transformation on mechanical properties. The effect of the martensitic transformation on the growth of austenite grains was also investigated. The result indicated that, with higher martensite content, alloy 2 possessed finer austenite grains and higher tensile strength. To compare the martensitic transformation behavior of the two steels, the Ms and Md30 temperatures, austenite stacking fault energies, and driving force were calculated by empirical equations. Equilibrium phase diagrams were calculated using Thermo‐Calc software. The kinetics of martensite volume fraction versus true strain was fitted by the sigmodal model. It was found that martensite volume fraction and deformation behavior exhibited significant differences in the two low‐nickel austenitic stainless steel. Both stacking fault energy and the driving force of transforming austenite to martensite have a critical role in strain‐induced martensite deformation. Beyond that, the prediction of martensite content by the sigmoidal equation was consistent with the experimental data. Abstract : Strain‐induced martensite transformation in the two austenitic stainless steel based on thermodynamic and kinetics calculations was investigated. The Ms and Md30 temperatures, austenite stacking fault energies, and driving force were calculated, and the kinetics of martensite volume fraction versus true strain were fitted by the sigmodal model.